2018
DOI: 10.7249/rr2658
|View full text |Cite
|
Sign up to set email alerts
|

Changes in What Teachers Know and Do in the Common Core Era: American Teacher Panel Findings from 2015 to 2017

Abstract: H ow much and how soon should we expect any federal or state education policy to improve student learning? The answer likely depends on the demands that the policy places on those who are expected to implement it and their capacity for change to meet those demands. The Common Core State Standards have been judged by many to be more challenging and ambitious than previous state standards (Porter et al., 2011; Shanahan, 2013; Brown and Kappes, 2012; Schmidt and Houang, 2012). Since the Common Core State Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Another nationally representative study found that the proportion of math teachers who regularly use the virtual resource pool TPT increased from 41% in 2015 to 60% in 2017. English teachers displayed a similar increase, from 42% to 55% (Kaufman et al, 2018). The proportion of regular Pinterest users remained stable and Google use declined over the same period, perhaps indicating that teachers are becoming more specialized in their searches for supplements.…”
Section: Systematic Reviewmentioning
confidence: 75%
See 1 more Smart Citation
“…Another nationally representative study found that the proportion of math teachers who regularly use the virtual resource pool TPT increased from 41% in 2015 to 60% in 2017. English teachers displayed a similar increase, from 42% to 55% (Kaufman et al, 2018). The proportion of regular Pinterest users remained stable and Google use declined over the same period, perhaps indicating that teachers are becoming more specialized in their searches for supplements.…”
Section: Systematic Reviewmentioning
confidence: 75%
“…Although supplementation is not a new phenomenon, the rise of virtual resource pools with millions of inexpensive, ready-made, always-available materials ranging in scope from single activities to full lesson and unit plans has contributed to sweeping “changes to the organizational ecology of curriculum materials” (Hodge et al, 2019, p. 426). These changes gave rise to large increases in teachers’ use of virtual resource pools, ushering in an era of easy access to supplemental materials that persists to this day (Kaufman et al, 2018). Commensurate with the rise of virtual resource pools, there has been a flurry of supplementation-relevant empirical research over the last half-decade.…”
mentioning
confidence: 99%
“…Our first data source is a supplemental section of the March 2019 American Teacher Panel (ATP) survey administered by RAND to state-representative samples of English Language Arts teachers in Louisiana, Massachusetts, and Rhode Island. (For more information about the general ATP survey, see Kaufman et al, 2018. ) There are 774 Kindergarten through high school teachers across 643 schools in the ATP sample we use.…”
Section: Datamentioning
confidence: 99%
“…is not yet consensus on exactly how to accomplish personalization, nor sufficient evidence on effectiveness for improving student outcomes (Pane, 2018). Studies by Pane et al (2017) are often interpreted as evidence of promise because they found modest positive effects on average across a set of schools implementing a diverse set of personalized learning models; however, the studies also found negative effects in about one-third of the individual schools in the sample, suggesting that the details of context or how personalized learning is implemented may be critical to success. Gross and DeArmond (2018) found considerable enthusiasm for personalized learning among educators, but also found that guidance, support, and materials were often insufficient to ensure consistent and rigorous implementation.…”
Section: Purpose and Design Of The Arimentioning
confidence: 99%
“…Similarly,Cook, Heath, and Thompson (2000) found an average 40-percent response rate among nearly 50 national survey studies. Among teachers in the RAND American Teacher Panel, a nationally representative survey panel, response rates range from roughly 50 to 65 percent (e.g.,Kaufman et al, 2018).…”
mentioning
confidence: 99%